The Effect of Dehydroepiandrosterone Treatment on Neurogenesis, Astrogliosis and Long-Term Cocaine-Seeking Behavior in a Cocaine Self-Administration Model in Rats - Ahdoot-Levi, Hadas; Croitoru, Ofri; Bareli, Tzofnat; Sudai, Einav; Peér-Nissan, Hilla; Jacob, Avi; Gispan, Iris; Maayan, Rachel; Weizman, Abraham; Yadid, Gal (Frontiers in Neuroscience, 2021)
Cocaine addiction is an acquired behavioral state developed in vulnerable individuals after cocaine exposure. It is characterized by compulsive drug-seeking and high vulnerability to relapse even after prolonged abstinence, associated with decreased neurogenesis in the hippocampus. This addictive state is hypothesized to be a form of “memory disease” in which the drug exploits the physiological neuroplasticity mechanisms that mediate regular learning and memory processes. Therefore, a major focus of the field has been to identify the cocaine-induced neuroadaptations occurring in the usurped brain’s reward circuit. The neurosteroid dehydroepiandrosterone (DHEA) affects brain cell morphology, differentiation, neurotransmission, and memory. It also reduces drug-seeking behavior in an animal model of cocaine self-administration. Here, we examined the long-lasting effects of DHEA treatment on the attenuation of cocaine-seeking behavior. We also examined its short- and long-term influence on hippocampal cells architecture (neurons and astrocytes). Using a behavioral examination, immunohistochemical staining, and diffusion tensor imaging, we found an immediate effect on tissue density and activation of astrocytes, which has a continuous beneficial effect on neurogenesis and tissue organization. This research emphasizes the requites concert between astrocytes and neurons in the rehabilitation from addiction behavior. Thus, DHEA may serve as a treatment that corrects brain damage following exposure to and abstinence from cocaine.